Why Speciesism is Wrong: A Response to Kagan. Issue 1 (2nd December 2015) - Singer, Peter
Abstract: In Animal Liberation I argued that we commonly ignore or discount the interests of sentient members of other species merely because they are not human, and that this bias in favour of members of our own species is, in important respects, parallel to the biases that lie behind racism and sexism. Shelly Kagan, in 'What's Wrong With Speciesism' misconstrues this argument, as well as the principle of equal consideration of interests, which I offer as an alternative to speciesism. Kagan also offers, as an alternative explanation of, and possible justification for, our discounting the interests of nonhuman animals, the suggestion that your interests count more if you are a member of a species whose typical adult members are persons. Although this view is not a form of speciesism, Kagan seems not to be aware of the fact that it is a view commonly defended by advocates of natural law ethics, on which there is already an extensive critical literature.